2003
DOI: 10.1034/j.1600-0838.2003.10288.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplements in Norwegian elite athletes—impact of international ranking and advisors

Abstract: we found that a similar percentage of female elite athletes and controls, but a higher percentage of male elite athletes than controls, reported the use of NS. There was a lower percentage of NS use among the top female athletes, but not the top male athletes as compared to the less successful elite athletes. The coach was the main advisor for NS use both for male and female elite athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
97
3
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 22 publications
21
97
3
7
Order By: Relevance
“…In the present study, the major motives for supplement use among athletes were to improve performance (78.0%) and increase lean mass (47.7%). These findings can partly explain why we found that whey protein was the most commonly consumed supplement, in agreement with the findings reported by Wiens et al [3], Sundgot-Borgen et al [12], and Giannopoulou et al [16].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the present study, the major motives for supplement use among athletes were to improve performance (78.0%) and increase lean mass (47.7%). These findings can partly explain why we found that whey protein was the most commonly consumed supplement, in agreement with the findings reported by Wiens et al [3], Sundgot-Borgen et al [12], and Giannopoulou et al [16].…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the results of other studies [8,12,16], we found that coaches are the primary source supplement recommendation for most athletes, and dietitians were their second main source of information, corroborating the findings among Saudi Arabian athletes [26] and Brazilian cyclists [20]. However, in most studies cited here, dietitians are not among the main three information sources [5][6][7]18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It has been consistently shown over the past few decades that a high number of athletes take dietary supplements [187][188][189][190][191][192][193][194][195][196]. caps.…”
Section: The Prevalence Knowledge and Attitudes Relating To Supplemementioning
confidence: 99%